Seasonal changes in composition and biomass of epiphytic algae on the macrophyte Ranunculus penicillatus in a chalk stream, with estimates of production, and observations on the epiphytes of Cladophora glomerata - Shamsudin, Lokman; Sleigh, Michael A. (Kluwer Academic Publishers, 1995)
The epiphytic algae on surfaces of the macrophyte Ranunculus penicillatus (Dumort.) Bab. var. calcareus (R. W. Butcher) C. D. K. Cook and on Cladophora glomerata (L.) Kütz growing in the River Itchen at Otterbourne near Southampton were studied between February 1984 and June 1985. The river at this site has a mean flow rate of 0.33 m s-1, and is about 16 m wide and on average 20 cm deep, with a discharge ranging through the year between 0.34 and 2.46 m3 s-1. The pH of the river varies little around 8.2, with a mean alkalinity of 236 mg HCOinf3sup1l-1, because of its origin from chalk springs. Ranunculus grows throughout the year, with peaks of biomass in spring and autumn. It forms a very large surface for attachment of epiphytes, and covers on average 40% of the stream bed. Numbers of epiphyte cells removed from Ranunculus ranged through the year between 52 × 103 and 271 × 103 cells mm-2 stream floor, with maximum numbers in April, and a secondary peak in October. This pattern partly reflects fluctuations in the biomass of Ranunculus; the number of cells per unit area of plant surface showed a broader spring peak and lower fluctuations in other seasons. Diatoms formed 65 to 98% of these epiphyte cells, with chlorophytes reaching their peak (10%) in summer and cyanophytes (25%) in autumn. Estimates of biomass of these epiphytic forms, derived from measurements of chlorophyll c, indicate a range between 30 and 100 g dry weight m-2 of weed bed. Colonisation studies showed that the algae grow and reproduce throughout the year, with a mean generation time of about 5 days, suggesting an annual production of about 3 kg dry weight m-2 of weed bed, which makes epiphytic algae the principal primary producers in the stream. The numbers and biomass of epiphytic algae on Cladophora are considerably less. The species of epiphytic algae found on Ranunculus were generally similar to those growing on Cladophora, and to epilithic algae on pebbles of the stream bed, but different species were dominant on the different substrata. Algal cells in the water column were all derived from benthic habitats, although their relative abundance was very different.